Autoethnographic Challenges: Confronting Self, Field and Home - Voloder, Lejla (The Australian journal of anthropology, 2008)
Anthropologists working at ‘home’ or in realms of the familiar often share a considerable sense of connection with participants. In these contexts, the researcher's potential position as an ‘insider’ offers particular opportunities for utilising self as a key resource. Through my own fieldwork at ‘home’ in Melbourne as an ‘insider’ among Bosnian migrants, I was confronted with the challenge of using my self to understand others' experiences. In this paper I discuss the autoethnographic process and consider how its application enabled me to consciously understand my own experiences and utilise my experiential self to inform my study.